Leadership and Employee Creativity: The Mediation Role of Intrinsic Motivation - I Nengah Aristana; Ni Made Dwi Puspitawati; Tjokorda Istri Tuty Ismayanthi (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
This study aims to analyze the effect of transformational leadership, entrepreneurial leadership, and intrinsic motivation on employee creativity and to investigate the role of intrinsic motivation as a mediation. This research was conducted in the export craft industry, with a quantitative approach. Collecting data using a questionnaire distributed to 114 employees, then the data is evaluated with SmartPLS 3.2.9. The results of the analysis show that transformational leadership is related to intrinsic motivation and employee creativity. While entrepreneurial leadership is related to creativity but not related to intrinsic motivation. Intrinsic motivation has been shown to mediate transformational leadership and not to mediate entrepreneurial leadership. These results can practically provide leaders with paying attention to intrinsic motivation to increase employee creativity.